2020
DOI: 10.1186/s12929-020-00634-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced NETosis generation in radiographic axial spondyloarthritis: utility as biomarker for disease activity and anti-TNF-α therapy effectiveness

Abstract: Background: Radiographic axial spondyloarthritis (r-axSpA) is a chronic inflammatory form of arthritis in which tumor necrosis factor (TNF)-α, a potent inducer of inflammatory response and a key regulator of innate immunity and of Th1 immune responses, plays a central role. NETosis is a mechanism of innate immune defense that is involved in diverse rheumatology diseases. Nevertheless, spontaneous NETosis generation in r-axSpA, its association to disease pathogenesis, and the NETosis involvement on anti-TNF-α t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Here, we found that peripheral neutrophils of active AS patients are highly prone to NETosis by showing an increased rate of NET formation in serum and ex vivo. Recently, Ruiz-Limon et al also reported increased levels of circulating NETosis-derived products in active AS patients further supporting our findings [35]. From a clinical point of view, surrogates of NET formation, such as serum levels of circulating cell-free DNA and MPO-DNA complexes, could be promising candidate markers in future large-scale studies assessing AS disease activity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Here, we found that peripheral neutrophils of active AS patients are highly prone to NETosis by showing an increased rate of NET formation in serum and ex vivo. Recently, Ruiz-Limon et al also reported increased levels of circulating NETosis-derived products in active AS patients further supporting our findings [35]. From a clinical point of view, surrogates of NET formation, such as serum levels of circulating cell-free DNA and MPO-DNA complexes, could be promising candidate markers in future large-scale studies assessing AS disease activity.…”
Section: Discussionsupporting
confidence: 89%
“…This is in agreement with experimental evidence demonstrating that IL‐1β plays a significant indirect role in IL‐17‐dependent MSC osteogenic differentiation, by activating ERK1/2, AKT, and STAT3 signaling pathways [44]. In addition, recent data describe a high accumulation of activated IL‐1β‐producing neutrophils in the paw joints during experimental spondyloarthritis [48], while plasma cell‐free DNA levels are positively correlated with IL‐1β concentration in active AS patients, further supporting the role of neutrophil‐derived IL‐1β in AS [35]. Recently, we reported the key pathogenic role of neutrophil/NET‐driven IL‐1β‐mediated inflammation in ulcerative colitis, a chronic inflammatory disease overlapping with the spondyloarthritis spectrum [30].…”
Section: Discussionmentioning
confidence: 95%
“…43,46 Of relevance, anti-TNF therapy reduces NET formation in vitro as well as in murine models and patients with immune mediated disease. [47][48][49]…”
Section: Netosis In Covid-19mentioning
confidence: 99%
“…A buffering mechanism similar to that observed for mast cells could be therefore postulated. In line with this consideration, one of the ways by which neutrophils promptly release the IL-17 in an inflammatory fashion is NETosis, previously observed in psoriasis and more recently reported to be exaggerated in radiographic axial SpA patients [ 107 , 108 ].…”
Section: Innate and Innate-like Immune Cellsmentioning
confidence: 66%